Hormones, psychotic disorders, and cognition in perinatal women: a mini review - Palacios-Hernández, Bruma; Ramírez-Alvarado, Gabriela; Téllez-Alanís, Bernarda; Lino-González, Ana Luisa; Penagos-Rivera, Miriam; Hernández-Galván, Adela (Frontiers in Psychiatry, 2024)
Previous scientific evidence has shown a relationship between hormones and the onset and relapse of perinatal psychotic disorders (PPD) in women during pregnancy, childbirth, and the postpartum period. In healthy women the interaction between hormones and cognitive changes has been confirmed mainly in memory, attention, and executive function during pregnancy and postpartum, which respond to adaptive demands related to parenting tasks. In women with psychotic episodes there is significant impairment in several cognitive functions, but studies of the perinatal period are limited. The objective of this mini review is to analyze the main findings to identify whether hormonal changes interact with the onset of PPD and cognitive impairment in perinatal women. The studies included samples of women with psychosis, risk of developing psychosis, bipolar psychosis, schizoaffective psychosis, and psychotic symptoms, during pregnancy and postpartum. Findings contributed to knowledge about five hypotheses regarding the relationship between hormones in the perinatal period and the appearance of PPD. Nevertheless, this review did not find reports of evidence of a relationship between hormonal production and cognitive function among women with clinically diagnosed PPD, suggesting a research gap. Clinical implications of assessing hormonal production and cognitive function in PPD are discussed. Although the evidence identified is scarce and heterogeneous, the findings call for further research with clinical samples on the role of hormones in perinatal psychotic disorders, especially as they relate to the study of cognition. This will promote more consistent evidence and understanding of PPD etiopathology that can guide early and effective multidisciplinary interventions.